Primer on outcomes research. Issue 5 (3rd July 2014) - In, Haejin; Rosen, Jennifer E.; Greene, Frederick L.; Rosen, Jennifer E.
<x xml:space="preserve">Abstract</x> Outcomes research uses diverse inputs to examine innovative end results aimed to deliver quality patient care. Yet defining "outcomes research" remains a challenge, and its interpretation is often nuanced. In this review, we discuss the definition of outcomes research in the context of its historical evolution along with the rise of other similar types of research. We then discuss key considerations in interpreting the results of outcomes analysis. J. Surg. Oncol. 2014 110:489–493. © 2014 Wiley Periodicals, Inc.